English in the Linguistic Landscape of Koh Lipe, Satun, Thailand: Lexis and Glocalization - Bennui, Pairote (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Koh Lipe, Satun is a famous tourist destination along the Andaman Sea, Southern Thailand where linguistic landscape is structured mainly in English. Monolingual, bilingual, and multilingual signage in this island displays distinctiveness of linguistic elements and linguistic diversity manifested in a variety of English lexicons. Thus, this study aims to analyze lexical characteristics of English in 370 signs along three popular beaches of the island – Pattaya Beach, Sunrise Beach, and Sunset Beach. It also discusses a reflection of the features on glocalization of English. Through the use of Linguistic Landscape, Multilingualism, and World Englishes approaches, an analysis of photographed data showed that textual formations of the signage highlight outstanding lexical and semantic dimensions of words. There appear to be English nouns, affixation, proper nouns in register of English, English compound nouns, hybrid compound nouns, acronyms, clipping, loanwords, loan translation, phrasal verbs, coinage, Tinglish words, and lexical repetition. Moreover, these lexical items present crucial linguistic formation in English that contacts other indigenous, Asian, and European languages, and they are formed to provide governmental information and to advertise local products and services of tourism for local and international tourists. Hence, these characteristics mirror glocalized English in a southern Thai context of tourism.